Education for democratic citizenship: the school which build bridges of humanity - Raffaele Beretta Piccoli (University of Bologna, 2021)
The article proposes two anthropological movements as guidelines for an education in democratic citizenship more capable of overcoming reductionisms and trivializations: a return to oneself, suggested by Hannah Arendt and a movement towards others, suggested by Edgar Morin. The text also takes the opportunity to formulate a reflection on the relevance of the global educational challenge of compulsory schooling for the construction of a more sensitive and open humanity.